Highly sensitive troponin T assay in normotensive patients with acute pulmonary embolism - Lankeit, Mareike; Friesen, Dietrich; Aschoff, John; Dellas, Claudia; Hasenfuß, Gerd; Katus, Hugo; Konstantinides, Stavros; Giannitsis, Evangelos (European heart journal, 2010)
To assess the role of cardiac troponin T (cTnT) levels on admission using a new, highly sensitive assay (hsTnT) in the risk assessment of normotensive patients with acute pulmonary embolism (PE).We prospectively studied 156 consecutive normotensive patients with confirmed PE. The prognostic value of hsTnT at baseline was compared with the conventional cTnT troponin assay and with N-terminal pro-brain natriuretic peptide concentrations. Long-term follow-up was available for 153 patients (98.1%). Highly sensitive troponin T values ranged from 0.001 to 357.2 pg/mL [median 27.2 (25th-75th percentile 9.4-69.4) pg/mL]. Overall, 100 patients (64%) had hsTnT ≥14 pg/mL. Baseline hsTnT was higher in patients with an adverse 30-day outcome (≥1: death, need for catecholamines, endotracheal intubation, or cardiopulmonary resuscitation) compared with an uncomplicated course [71.7 (35.5-117.9) vs. 26.4 (9.2-68.2) pg/mL; P = 0.027]. The cut-off value of 14 pg/mL showed an excellent prognostic sensitivity and negative predictive value (both 100%). In comparison, as many as 50% of the patients with an adverse early outcome would have been misclassified as low risk by cTnT (cut-off 0.03 ng/mL). Logistic regression indicated a two-fold increase in the risk of an adverse outcome for each increase of hsTnT by 1SD of the natural logarithm (P = 0.037). Patients with elevated hsTnT levels had a reduced probability of long-term survival (P = 0.029 by log-rank); by Cox's regression analysis, hsTnT was the only laboratory biomarker predicting an elevated risk of death over the long term.Highly sensitive troponin T assays may be capable of improving risk stratification of non-high-risk PE.